Multi-objective Optimization of LARP Parameters using Weighted Sum DE Method - Seyedi, Behnam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: This thesis employed the single-objective differential evolution (DE) algorithm to search the multi-objective solutions to obtain lateral controller (LARP) settings for an auto-steered tractor by combining two fitness functions, lateral peak and RMS errors, to a single objective using the weighted-sum-method. Compared to the multi-objective differential algorithm, weighted-sum DE algorithm covered a larger range of the Pareto-front. After modifying DE to set the search space adaptively, the modified method finds better non-dominated solutions than MODE by less number of fitness evaluations. Weighted Sum DE algorithm obtained better non-dominated solutions than MODE algorithm although weighted sum DE uses 20 000 fitness evaluation while MODE used 500 000 evaluations. Keywords: Weighted sum optimization, LARP control, Automatic steering agricultural vehicle. ………………………………………………………………………………………………………………………… ÖZ: Bu tezde otomatik sürüşlü bir traktörün tepe ve RMS hata olmak üzere iki objektifli en iyi LARP denetleci ayarlarını bulmak için tek-objektifli farksal evrim algoritması, iki objektifi ağırlıklı toplam yöntemiyle tek objektife indirerek kullanıldı. Çok objektifli farksal evrim algoritması MODE ile karşılaştırıldığında ağırlıklı toplamlı DE algoritmasının Pareto-önde daha geniş bir aralığı doldurduğu görülmüştür. Ağırlıklı toplamlı DE yönteminde arama uzayını adaptif olarak ayarlayacak değişikliklerden sonra oluşturulan yöntem MODE nin bulduğu çözümlerden daha iyi baskın olmayan çözümleri daha az uyum değerlendirmesi ile bulabilmektedir. Ağırlıklı toplamlı DE’nin 2000 uyum değerlendirmesiyle bulduğu çözümlerin MODE’nin 500000 uyum değerlendirmesiyle bulduklarından daha iyi olduğu gözlenmiştir. Anahtar Kelimeler: Ağırlıklı toplamlı optimizasyon, LARP kontrol, Otomatik sürüşlü tarımsal araç.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2014. Supervisor: Assist. Prof. Dr. Mehmet Bodur.
Keywords: Computer Engineering; Weighted sum optimization, LARP control, Automatic steering agricultural vehicle